2023
DOI: 10.1155/2023/5839776
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality of Life in Residential Aged Care Using the EQ-5D-5L: A Cross-Sectional Study on the Impact of Cognition Level and Proxy Perspective on Interrater Agreement

Abstract: Quality of life (QoL) is an important outcome in aged care, but self-report is not always possible due to the high prevalence of cognitive impairment in older aged care residents. This study aims to assess the impact of family member proxy perspective (proxy-proxy or proxy-person) on interrater agreement with resident self-report by different cognition levels. The influence of proxy perspective and cognition level is a significant gap in the extant literature which this study seeks to address. A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A recent review suggested there may be stronger agreement on more observable quality-of-life domains e.g., physical health and mobility, than with, for example, anxiety/depression, emotional well-being 36 but perhaps this tendency is mitigated when proxies are repeatedly reminded to respond from the person's perspective. 37 Other measures related with quality of life, either generic (EQ-5D, ICECAP-O) or disease-specific (DEMQOL), were also considered for EU-Actifcare reports, where crossvalidating quality-of-life tools in dementia was also a (secondary) aim. Analyzing the small subsample of the present study, we only reported QOL-AD results, the disease-specific measure with more in-depth documentation of validity and test-retest reliability in Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggested there may be stronger agreement on more observable quality-of-life domains e.g., physical health and mobility, than with, for example, anxiety/depression, emotional well-being 36 but perhaps this tendency is mitigated when proxies are repeatedly reminded to respond from the person's perspective. 37 Other measures related with quality of life, either generic (EQ-5D, ICECAP-O) or disease-specific (DEMQOL), were also considered for EU-Actifcare reports, where crossvalidating quality-of-life tools in dementia was also a (secondary) aim. Analyzing the small subsample of the present study, we only reported QOL-AD results, the disease-specific measure with more in-depth documentation of validity and test-retest reliability in Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…In the proxy-proxy perspective, the proxy rates the health of the PlwD from their own perspective. 8 Studies have examined the agreement between self-and proxyreports using the preference-based EuroQol 5 Dimension survey (EQ-5D) questionnaire, recommend by health technology assessment agencies (HTA) and used in dementia research. [9][10][11] In its simplicity and shortness, the EQ-5D is a commonly used instrument in interventional and health economic studies, available and validated in different languages.…”
Section: Introductionmentioning
confidence: 99%
“…In the proxy‐proxy perspective, the proxy rates the health of the PlwD from their own perspective. 8 …”
Section: Introductionmentioning
confidence: 99%